PENGARUH AUDIT TENURE, MORAL REASONING, INDEPENDENSI, DAN FEE AUDIT TERHADAP KUALITAS AUDIT - Ni Putu Lisa Ernawatiningsih; Ni Nyoman Ayu Suryandari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2025)
Audit quality is a crucial aspect in maintaining the reliability of financial reports and public trust in the public accounting profession. A quality audit ensures that a company's financial statements are presented fairly and are free from material errors, whether intentional or unintentional. In this context, a Public Accounting Firm (KAP) acts as an independent party, providing assurance to stakeholders regarding the credibility of a company's financial information. This study was conducted with the aim of knowing the Effect of Accountability, Due Professional Care, Audit Tenure, Moral Reasoning, Independence, and fee audit on Audit Quality at Public Accounting Firms in Bali Province. The data used in this study are primary data. This study uses data collection techniques using a questionnaire. The sampling method in this study was purposive sampling. The data analysis used in this research is multiple linear regression. The results of this study indicate that the variables of Audit Tenure and Fee Audit have a positive and significant effect on audit quality, while the variables of Moral Reasoning and Independence have no effect on audit quality in Bali Province.